Proposed new interior design of youth community centre at Lot 22061 (No. Lot Baru) Taman Nong Chik, Mukim Bandaran, Daerah Johor Bahru, Johor Darul Takzim / Khairul Akmal Sulaiman Md Tahir - Md Tahir, Khairul Akmal Sulaiman (Faculty of Architecture, Planning and Surveying, 2012)
A final year students of diploma in Interior Architecture area required to prepare a final year project. The project that has been selected by the student should be related to the current issue in scope of general and design issues. The skills and knowledge are required during the duration of the semester or course should be applied onto the drawings and presentation boards. This is include building and site analysis or research, conducted case studies, interviewed with client, designed proposals, preparing drawings, design development, and not to forget, preparing final presentation boards and final assessment by the panels during final presentation. The proposed client or product for this project is ‘JOHO’ and the idea is to propose new interior design of community centre at Lot 22061 Taman Nong chik, Mukim Bandaran, Daerah Johor Bahru, Johor Darul Takzim for JOHO. The proposal is to fulfil client’s needs at the same time give facilities to public especially to young generation. From the observation, interview and research that have been conducted, The information are gathered and use as a guideline during design process and to create suitable, functional and systematic design for users. The objective is to design a community centre for JOHO as a place for teenagers to gather under one roof and involve in various activities at the same time as a place for these young generation to express their talents in any categories relate to lifestyle such as music, arts, design, sports, or culture and heritage. It is sincerely hope that this propose design could solve the related issues at the same time reflected the identity corporate image of the client.